ANTIBACTERIAL ACTIVITY OF EUCALYPTUS GLOBULUS ESSENTIAL OIL FRACTIONS AGAINST ANTIBIOTIC RESISTANT ENTEROCOCCUS FAECIUM ISOLATED FROM DIARRHEIC SHEEP - T. Ali; A. A. Anjum; S. S. Abdelgayed; A. Sarwar; M. M. K. Sattar; M. Naveed; M. Tariq (Journal of Animal and Plant Sciences, 2023)
Antibiotic resistant Enterococcus faecium isolated from the diarrheic sheep were subjected to antibacterial activity of plant essential oils and their fractions. The fraction with least minimum inhibitory concentration (MIC) was subjected to cytotoxicity and gas chromatography-mass spectrometry (GCMS) analysis. Primarily, biochemically characterized isolates were confirmed by PCR amplification of 16S rRNA gene followed by nucleotide sequencing and accession numbers received were MW332526.1, MW332527.1, MW332528.1 and MW332529.1. These isolates were screened for antibiotic resistance to a variety of antibiotic classes and recorded as resistant to all the tested antibiotics. Antibacterial activity of plant essential oils (n=05) was checked against three selected antibiotic resistant E. faecium isolates. Activity of Eucalyptus globulus was highest (13.00±1.3 mm) and among the fractions of E. globulus, n-hexane plus chloroform depicted a higher mean zone of inhibition (13.45±1.11mm) with least MIC (25.28±7.41 mg/mL) which differed significantly (P<0.05) with other fractions tested. Cell survival percentage was 58.60 at 112.10 mg/mL concentration. GCMS analysis revealed that the highest percentage (14.4%) was of Bicyclo[2.2.1]heptan-2-ol,1,7,7-trimethyl. It was concluded that E. globulus fraction n-hexane plus chloroform showed significantly (P<0.05) better results as compared to other (n=08) E. globulus solvent fractions for treatment of antibiotic resistant cases of diarrhea in sheep caused by E. faecium.
Keywords: Antibiotic resistance; Enterococcus faecium; Eucalyptus globulus fractions; Cell survival percentage; Gas chromatography-mass spectrometry